REMOVAL OF CD2+ FROM WATER BY USE OF SUPER-MACROPOROUS CRYOGELS AND COMPARISON TO COMMERCIAL ADSORBENTS - Baimenov, Alzhan; Berillo, Dmitriy; Azat, Seitkhan; Nurgozhin, Talgat; Inglezakis, Vassilis J. (MDPI, 2020)
In this study amphoteric cryogels were synthesized by the use of free-radical co-polymerization of acrylate-based precursors (methacrylic acid and 2-acrylamido-2-methyl-1-propansulfonic acid) with allylamine at different ratios. The physico-chemical characteristics of the cryogels were examined using SEM/EDX, FT-IR, XPS and zeta potential measurements. The cryogels were tested toward Cd2+ removal from aqueous solutions at various pH and initial concentrations. Equilibrium studies revealed a maximum sorption capacity in the range of 132–249 mg/g. Leaching experiments indicated the stability of Cd2+ in the cryogel structure. Based on kinetics, equilibrium and characterization results, possible removal mechanisms are proposed, indicating a combination of ion exchange and complexation of Cd2+ with the cryogels’ surface functional groups. The cryogels were compared to commercially available adsorbents (zeolite Y and cation exchange resin) for the removal of Cd2+ from various water matrices (ultrapure water, tap water and river water) and the results showed that, under the experimental conditions used, the cryogels can be more effective adsorbents.
Keywords: cryogels; adsorption; ion-exchange; complexation; cadmium; water treatment; Type of access: Open Access